The Significance of Life Insurance Sale Management for the Development of the Financial Market - Nikolić, Milena; Milojković, Danka; Jemović, Mirjana (Annals of Spiru Haret University. Economic Series, 2023)
Life insurance companies as institutional investors are key participants in the global financial market. By collecting the savings of the insured, accumulating large amounts of funds and their long-term investment into various financial instruments, these companies affect the development and stability of the financial market. Considering their significance, the aim of this paper is to determine the determinants of life insurance demand by analysing the environment in which these companies operate on the European financial markets, in order to detect the possibilities for increasing the sale of life insurance policies, and thus the amount of collected amount that will be invested in the financial market for a long term. Based on the research results, determinants that may encourage the life insurance demand in European countries are determined and the recommendations on how to manage the sale of life insurance policies, with the aim of increasing the amount of collected funds.